Traffic Accident Risk Analysis by Knowledge, the Use of Traffic Lane, and Speed - Annisa Hidayati; Lucia Yovita Hendrati (Jurnal Berkala Epidemiologi, 2016)
The number of traffic accidents has increased every year. Traffic accidents are the third largest killer in Indonesia after coronary heart disease and tuberculosis in Indonesia. Traffic accidents mostly involve motorcycle riders, including junior high school students. This research was conducted to determine the relationship of knowledge, use of lanes, and driving speed with traffic accident events in junior high school motorcycle riders. This type of research is an observational analytic cross-sectional study design. The population of this study was all junior high school students in Wonokromo Sub-district Surabaya in 2015. The number of respondents in this study was 100 respondents drawn from the population using the two-stage cluster random sampling method. The variables studied were knowledge, use of the lane, and driving speed. The results of the analysis using the chi-square test showed that knowledge (p = 0.027; RR = 1.966), use of the lane (p = 0.005; RR = 1.894) and driving speed (p = 0.017; RR = 1.941) had a significant relationship to the incidence of traffic accidents in junior high school students motorbike riders in Wonokromo Sub-district Surabaya in 2015. Children under 17 years of age especially junior high school students are advised not to ride a motorcycle before having a Driving License. The role of parents, teachers, and law enforcement to prevent motorbike riders under the age of 17 is very much needed in minimizing the number of motorcycle accidents involving junior high school students.